Fortuitous synthesis of unsaturated half-sandwich Ruthenium(II) complexes via solvent-involved rearrangement and their biological evaluation. (January 2021) - Yang, Yanjing; Guo, Lihua; Huang, Jie; Ji, Mingjun; Ge, Xingxing; Chen, Wenjing; Zhou, Huanxing; Li, Xin; Tuo, Shujing; Liu, Zhe
Abstract: A series of unsaturated (16-electron) five-coordinated ruthenium (II) complexes of the type [( η 6 -arene)Ru(N^N)] + PF6 −, where N^N is aminoimine and η 6 -arene is benzene (bz) (Ru1 ), 3-phenylpropan-1-ol (bz-PA) (Ru2 ), or 4-phenylbutan-1-ol (bz-BA) (Ru3 ), respectively, have been serendipitously synthesized via solvent (methanol)-involved rearrangement. The identity and purity of these new complexes were determined by NMR spectroscopy, elemental analysis, mass spectrometry, and X-ray crystallography techniques. Their fluorescence property and electrochemical behavior were also investigated. These complexes showed sufficient stability and exhibited higher anticancer activity toward A549 human lung cancer cells, human cervical carcinoma cells (HeLa) and hepatocellular carcinoma cell (HepG2) than cisplatin. The investigation of structure-activity relationship displayed that Ru1 with the hydrophobic groups exhibited enhanced anticancer activity in comparison to Ru2 and Ru3 containing hydroxyl groups. Notably, complex Ru1 entered A549 human lung cancer cells through a non-energy-dependent pathway and mainly accumulated in lysosomes. Moreover, Ru1 induced a dose-dependent apoptosis and sub-G1 fraction perturbation. Graphical abstract: Image 1 Highlights: Unsaturated fluorescent ruthenium(II) complexes have been synthesized via solvent-involved rearrangement. These complexes mainly accumulate in lysosomes and induce lysosomal damage. The structure-activity relationship of these complexes is significant.